Integrative Relationship between the Picture and the Written Text in the Commercial Advertisement (Al-Academy, 2018)
There is no doubt that the advertisement picture and the written text play a key role in the formation of the language of the communicative discourse as the main pillars of the design of commercial advertising and the main entrance for the advertising message awareness... Hence the researcher chose the title of her research (Integrative Relationship between the Picture and the Written Text in the Printed Commercial Advertisement) starting from following questions: What is the relationship between the picture and the written text in the printed commercial declaration? Is there functional, aesthetic and interactive integration between them? The importance of the research stems from the possibility of its contribution to the enrichment of the cognitive aspect of the complementarity of the relationship between the picture and the written text in the design of the printed commercial advertisement for the specialists researchers and workers and those interested in the field of design. The research also aims at revealing the integration of the relationship between the picture and the written text in the design of the printed commercial advertisement. The research limits were determined to the study of commercial advertisements of the United States of America published on the Internet in 2016. The theoretical framework of the research included the problem of research, its importance, its objectives, and its objective, temporal and spatial limits. The theoretical framework included two sections: the first section is about the concept of complementarity in the typographic achievement. The second section dealt with the effectiveness of the relationship between the picture and the written text in the commercial advertisement. The research procedures and the most important findings and conclusions are then presented. The most important results that have been achieved are as follows: 1 – The employment of the advertising picture as the main unit that occupies the majority of the advertising space, while the written text explains and supports it, achieving a coherent relationship between the visual and intellectual situation. 2 –The presence of words alongside the picture helps in opening the horizons to the thinking of the recipient, especially in the case of words compensation for the inability of the fixed advertisement picture in the expression of temporal or causal links